Barriers and Opportunities for International Brands in Oman: between a Traditional Market Souk and a Shopping Mall - Chęś, Agnieszka (Studia Oeconomica Posnaniensia, 2017)
The Sultanate of Oman is an emerging market with a considerably high GDP per capita. Nevertheless the expansion of shopping malls in the Sultanate began only after 2012, giving opportunities for the entrance of many international brands. The paper describes how for many years the entrance of international brands has been hindered by the slow development of retail and the attachment of local people to shopping in traditional souks and small shops. The paper analyses changes in the structure of retail after 1970 and describes the economic, social and cultural reasons behind it. The capital city of Muscat is used for the analysis, being the most important and at the same time a representative center of retail in the country.